(untitled) (Research, Society and Development, 2023)
Introduction: The assessment of nutritional status at different stages of life is important for establishing risk situations, nutritional diagnosis and planning actions for health promotion and disease prevention. In children, its importance is given both for monitoring growth and health, and for early detection of nutritional disorders, be it malnutrition, obesity, among others. Objective Describe the nutritional status of children from 0 to 5 years of age monitored at the Primary Health Care Units (UAPS) in the municipality of Igaratinga-MG between 2019 and 2021. Methodology This is a descriptive study in which secondary data accessed in the public access mode of the Food and Nutrition Surveillance System (Sisvan Web). Result: Between 2019 and 2021, the extremes of nutritional status in children, which include thinness and short stature, as well as overweight, increased proportionally, while eutrophy and adequate height decreased. This result can be attributed to the pandemic period, in which, with social isolation, the population stayed away, generating several negative impacts, on the one hand, reducing energy expenditure due to sedentary lifestyle and consumption of ultra-processed foods, and on the other hand, due to the increase in food insecurity. Conclusion: It is necessary to implement public policies to prevent nutritional problems related to the nutritional status of children during the COVID-19 pandemic, as well as to promote food and nutrition education actions in schools.